Ga crystallization dynamics during annealing of self-assisted GaAs nanowires. (20th December 2016) - Scarpellini, David; Fedorov, Alexey; Somaschini, Claudio; Frigeri, Cesare; Bollani, Monica; Bietti, Sergio; Nöetzel, Richard; Sanguinetti, Stefano
Abstract: In As atmosphere, we analyzed the crystallization dynamics during post-growth annealing of Ga droplets residing at the top of self-assisted GaAs nanowires grown by molecular beam epitaxy. The final crystallization steps, fundamental to determining the top facet nanowire morphology, proceeded via a balance of Ga crystallization via vapor-liquid-solid and layer-by-layer growth around the droplet, promoted by Ga diffusion out of the droplet perimeter, As desorption, and diffusion dynamics. By controlling As flux and substrate temperature the transformation of Ga droplets into nanowire segments with a top surface flat and parallel to the substrate was achieved, thus opening the possibility to realize atomically sharp vertical heterostructures in III-As self-assisted nanowires through group III exchange.